ANALISIS EFEKTIVITAS KECEPATAN KAPAL KATAMARAN MV. LAGANBAR MENGGUNAKAN CENTREBULB BERBENTUK FOIL SEBAGAI KOMPONEN PENURUNAN HAMBATAN KAPAL - Airlangga Richard Harsono Putra, (2023)
A catamaran is a ship with a double hull. With this innovation, of course, it can cause advantages and disadvantages compared to the previous one. Theoretically, catamarans have better stability, but the resistance on catamarans tends to be greater because there are waves that hit the catamaran hull. The solution to this problem is to provide a new component, namely centrebulb. In this study, the centrebulb, which functions as a decrease in the resistance of the ship, was varied in terms of shape and position, as well as variations in the appropriate speed for using the centrebulb on catamarans. The shape used is the foil shape (NACA 0030) with 3 different x-axis positions and 5 speeds from medium to high. In this study there is an analysis of fluid flow and wave interference between the two hulls to show the effectiveness of the right speed and also a decrease in ship resistance using an analysis approach through CFD software, namely Ansys CFX. As a result, of the 15 variations that have been simulated, the best centrebulb configuration for reducing ship resistance is the 2nd variation, with the centrebulb positioned in the middle at a speed of Fn 0.35 which has a resistance value of 1.08.